Evaluation of a project to enhance knowledge of hereditary diseases and management. Issue 10 (October 1997) - Walpole, I R; Watson, C; Moore, D; Goldblatt, J; Bower, C
Abstract : During 1992 and 1993, in a designated suburban area of Perth, Western Australia, information on hereditary disease was provided for health professionals and the general community. This information was in the form of posters, pamphlets, postal flyers and return letter cards, a static display, newspaper articles, advertisements and radio broadcasts, and professional seminars. The aim of this project was to evaluate the effectiveness of combined strategies to convey practical information about hereditary disease to the community and health professionals. Multiple measures of response evaluation were used, which included structured questionnaire surveys of health professionals and members of the community before and after the project. In the community surveys, respondents who were female, married, middle aged, and parents, and had a higher level of education or were born in Australia, New Zealand, or the United Kingdom were generally better informed about hereditary diseases. This intervention resulted in only meagre changes in community knowledge about hereditary disease, even though promotional materials were shown to be appropriate. General Practitioners (GPs) and Child Health Nurses (CHNs) were supportive of clinical genetic services and recognised a need for continuation of education in this field. There is a rapidly increasing need for community and health professional comprehension of the applications of the new genetic technology. This project indicates that routine educational and health promotion strategies will not be enough to achieve desired levels of knowledge and attitude change.